IMPROVING GRAMMAR AND VOCABULARY THROUGH WAYGROUND: A QUASI-EXPERIMENTAL STUDY - Nurfitrah Nurfitrah; Ambo Dalle; Abdul Haris Sunubi; Arqam Arqam; Magdahalena Tjalla (International Journal of English Education and Linguistics (IJoEEL), 2026)
Grammar and vocabulary are fundamental components of English proficiency, as they underpin learners’ ability to comprehend and produce meaningful language across all skills. However, despite their importance, classroom practices, particularly in junior high schools, often rely on conventional assessment methods that provide limited engagement and delayed feedback, resulting in suboptimal learning outcomes. Although previous studies have highlighted the potential of gamified digital platforms such as Wayground to increase student motivation, empirical evidence measuring their direct impact on grammar and vocabulary achievement remains limited, especially in Indonesian secondary education contexts. This study aimed to examine the effectiveness of the Wayground application in improving students’ grammar and vocabulary mastery. Employing a quasi-experimental design with a non-equivalent control group, the study involved eighth-grade students at MTs DDI Baru Polman, divided into an experimental group taught using Wayground and a control group taught through conventional methods. Data were collected through pretests and post-tests and analyzed using the Mann–Whitney U test due to non-normal data distribution. The findings revealed a statistically significant difference between the two groups, with the experimental group achieving higher post-test scores (M = 77.44) than the control group (M = 65.12), and a moderate effect size (r = 0.352). These results indicate that Wayground is more effective than traditional instruction in enhancing students’ grammar and vocabulary achievement. Therefore, Wayground can be considered a viable digital assessment tool to support grammar and vocabulary learning in junior high school English classrooms.